Effects of Microbiota-Driven Therapy on Circulating Trimethylamine-N-Oxide Metabolism: A Systematic Review and Meta-Analysis - Miao, Lina; Du, Jianpeng; Chen, Zhuhong; Shi, Dazhuo; Qu, Hua (Frontiers in Cardiovascular Medicine, 2021)
Aim This study was designed to systematically evaluate the effects of microbiota-driven therapy on decreasing TMAO and its related metabolites. Methods and results PubMed, EMBASE and Cochrane Library databases were searched (up to July 2021). Randomized controlled trials (RCTs), compared microbiota-driven therapy (prebiotics, probiotics, or synbiotics) with placebo on decreasing TMAO and its related metabolites, were eligible. Two researchers extracted the data independently and the disagreement was resolved by a third researcher. The risk of bias of included study was evaluated using Cochrane tool (RoB 2.0). Meta-analysis, meta-regression analysis and publication bias analysis were performed by RevMan 5.3 or Stata 12.0 software. Ten studies (12 arms) involving 342 patients (168 patients in the intervention group and 174 patients in the control group) were included. Compared with the control group, microbiota-driven therapy did not reduce circulating TMAO [SMD=-0.05, 95%CI (-0.36,0.26), P=0.749], choline [SMD=-0.34, 95%CI (-1.09,0.41), P=0.373], betaine aldehyde [SMD=-0.704, 95%CI (-1.789,0.382), P=0.204], and L-carnatine [SMD=-0.06, 95%CI (-0.38,0.25), P=0.692]. Conclusion Current evidence does not support that microbiota-driven treatment reduce circulating levels of TMAO, choline, betaine aldehyde, and L-carnitine. However, given the small sample size, this conclusion needs to be proved in the future.